Hydrogen storage alloys : with RE-Mg-Ni based negative electrodes - Han, Shumin; Li, Yuan; Liu, Baozhong (De Gruyter, 2017)
The book presents current research progress on hydrogen storage alloys, with a special focus on their applications in batteries. Background, formation mechanisms, electrochemical characteristics, and effects of elemental substitution are covered. Provides an up-to-date overview of the theme for experienced researchers, while including enough fundamentals to serve as a handy, practical introduction for newcomers to the field.